Being for evaluating the semantic program of expressivism - Schroeder, Mark Andrew, 1977- (Oxford : Clarendon, 2008)
Mark Schroeder explores the semantic commitments of metaethical expressivism, the heir to the noncognitivist theories of Ayer Stevenson, and Hare. He shows how to solve many of the open problems facing expressivism, but this only highlights further and deeper problems for the view.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Expression (Philosophy); Semantics (Philosophy)